rozwiąż równania
A)0,3x-2,6=1,5x+2,2
B)0,4+2,5x=2,5x-4
C) 0,6x-2,2=5x+1,1
D)-2x+5=0,4x+0,2
E)-2(x-2,8)=3,4x+0,2
F)0,2(5+0,3x)=0,06x+1
G)6(0,1x-0,2)=3(x+0,8)
H)0,4(x-6)=0,2(3x+5)​


Odpowiedź :

Odpowiedź:

A) 0,3x-2,6=1,5x+2,2

0,3x-1,5x=2,2+2,6

-1,2x=4,8

x=-4

B) 0,4+2,5x=2,5x-4

2,5x-2,5x=-4-0,4

x=-4,4

C)0,6x-2,2=5x+1,1

0,6x-5x=1,1+2,2

-4,4x=3,3

x=-3,3/4,4

x=-33/44

x=-0,75

D) -2x+5=0,4x+0,2

-2x-0,4x=0,2-5

-2,4x=-4,8

x=2

E) -2(x-2,8)=3,4x+0,2

-2x+5,6=3,4x+0,2

-2x-3,4x=0,2-5,6

-5,4x=-5,4

x=1

F)0,2(5+0,3x)=0,06x+1

1+0,06x=0,06x+1

0,06x-0,06x=1-1

x=0

G)6(0,1x-0,2)=3(x+0,8)

0,6x-1,2=3x+2,4

0,6x-3x=2,4+1,2

-2,4x=4,8

x=-2

H)0,4(x-6)=0,2(3x+5)

0,4x-2,4=0,6x+1

0,4x-0,6x=1+2,4

-0,2x=3,4

x=-1,7

Szczegółowe wyjaśnienie: